Humidifying laminate and humidifier

By using porous reinforcement materials and hydrophobic concave-convex shaped non-porous membranes in the humidifier, the problem of enlargement and cost increase caused by adhesion of moisture-permeable membrane humidifiers is solved, and the humidifier is miniaturized and cost-effective. reduce.

CN119343232APending Publication Date: 2025-01-21DAICEL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380045951.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing moisture permeable membrane humidifiers need to set a gap between the non-porous moisture permeable membranes sealed into the porous plate to avoid adhesion, resulting in larger and increased cost of humidifiers.

Method used

A porous reinforcing material is laminated with a non-porous membrane, and the surface of the non-porous membrane is hydrophobic and has a concave-convex shape, and contains an anti-adhesive agent to inhibit adhesion between the non-porous membranes.

Benefits of technology

Effectively suppresses adhesion between non-porous membranes, miniaturizing the humidifier and reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343232A_ABST
    Figure CN119343232A_ABST
Patent Text Reader

Abstract

Provided is a humidification laminate which is capable of suppressing adhesion between nonporous films. A humidification laminate (1) is provided with a porous reinforcing material (11) and a non-porous film (12) which is laminated on at least one surface of the porous reinforcing material (11) and functions as a moisture-permeable film, and the surface of the non-porous film (12) has water repellency and has an uneven shape. In addition, the non-porous membrane (12) preferably contains an anti-blocking agent. Furthermore, it is preferable that the average particle diameter of the anti-blocking agent is larger than the film thickness of the non-porous film (12), and that the uneven shape is formed from the anti-blocking agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a humidifying laminate and a humidifier. In addition, this application claims priority to Japanese Patent Application No. 2022-096879 filed in Japan on June 15, 2022, the contents of which are incorporated herein by reference. Background Art

[0002] In the case of a moisture permeable membrane type humidifier, since only water vapor passes through the moisture permeable membrane, the humidified air does not come into direct contact with water, thereby suppressing the scattering of bacteria and scale components. In order to improve the moisture permeability performance of such a moisture permeable membrane type humidifier, research has been conducted to expand the area of ​​the moisture permeable membrane. For example, a form in which a three-dimensional porous plate is sealed in a non-porous moisture permeable membrane is known, such as Patent Document 1.

[0003] The structure using a three-dimensional porous plate as in Patent Document 1 can increase the surface area of ​​the moisture permeable membrane in contact with water, thereby improving the moisture permeability.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 8-233315 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In the humidifier of Patent Document 1, in order to exert the air supply performance, it is necessary to provide a gap between the non-porous moisture permeable membranes sealed with a porous plate. The reason is that, in the absence of a gap, the non-porous membranes contact and adhere to each other, which may impair the air supply performance. However, in Patent Document 1, since a gap is provided between the non-porous moisture permeable membranes, there is a disadvantage that the humidifier needs to be enlarged. In addition, if the humidifier is enlarged, there is also a problem of increased cost.

[0009] Therefore, an object of the present disclosure is to provide a humidifying laminate that solves such a problem and can suppress the blocking of non-porous films.

[0010] Solutions for solving problems

[0011] The inventors of the present disclosure have conducted in-depth research to achieve the above-mentioned purpose, and found that the following humidification laminate can inhibit the adhesion of non-porous films, wherein the humidification laminate has: a porous reinforcing material; and a non-porous film, which is laminated on at least one surface of the porous reinforcing material and functions as a moisture-permeable film, and the surface of the non-porous film has hydrophobicity and a concavo-convex shape. The present disclosure relates to a substance completed based on these insights.

[0012] That is, the present disclosure provides a humidifying laminate, wherein the laminate comprises: a porous reinforcing material; and a nonporous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, wherein the surface of the nonporous film is hydrophobic and has a concavo-convex shape.

[0013] The surface of the nonporous film of the humidifying laminate is water-repellent and has an uneven shape, thereby being able to suppress the nonporous films from sticking together.

[0014] The nonporous film preferably contains an anti-blocking agent. By containing the anti-blocking agent, it is easy to suppress the blocking of the nonporous films.

[0015] Preferably, the average particle size of the anti-blocking agent is larger than the thickness of the non-porous film, and the concavo-convex shape is formed by the anti-blocking agent. By making the average particle size of the anti-blocking agent larger than the thickness of the non-porous film, it is easy to form a concavo-convex shape on the surface of the non-porous film.

[0016] The water contact angle of the nonporous membrane surface is preferably 90° to 120°. When the water contact angle of the nonporous membrane surface is within the above range, water repellency is easily exhibited.

[0017] The arithmetic mean roughness (Sa) of the nonporous film surface is preferably 0.1 μm to 0.5 μm. When the arithmetic mean roughness (Sa) of the nonporous film surface is within the above range, it is easy to suppress the blocking of the nonporous films.

[0018] Furthermore, the non-porous membrane is preferably disposed on the water side of the liquid relative to the porous reinforcing material so as to absorb water from the liquid and release it into the air.

[0019] Preferably, the non-porous film contains a thermoplastic resin having a cationic portion, wherein the cationic portion contains a group containing an ammonium ion or a group capable of forming an ammonium ion. By containing a group containing an ammonium ion or a group capable of forming an ammonium ion, the non-porous film can exert a bactericidal effect, thereby inhibiting the attachment / accumulation of miscellaneous bacteria and the like.

[0020] Preferably, the nonporous film contains a thermoplastic resin having a hydrophilic portion, wherein the hydrophilic portion contains a structural unit represented by the following formula (1). By providing the nonporous film with the hydrophilic portion of the structural unit, a water conduction path can be formed in the nonporous film, and moisture permeability can be easily exhibited.

[0021] [Chemical formula 1]

[0022]

[0023] (R1 and R2 each independently represent a hydrogen atom or a methyl group.)

[0024] In addition, it is preferred that the nonporous membrane contains a thermoplastic resin having a hydrophobic portion, wherein the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3). By making the nonporous membrane have the hydrophobic portion of the structural unit, the surface of the nonporous membrane can exhibit hydrophobicity.

[0025] [Chemical formula 2]

[0026]

[0027] (R1 represents a hydrogen atom or a methyl group, and R3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms.)

[0028] [Chemical formula 3]

[0029]

[0030] (R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.)

[0031] In addition, the water retention capacity of the humidification laminate is preferably 5 g / m 2 ~30g / m 2 By setting the water retention amount to be within the above range, sufficient moisture permeability can be easily exhibited.

[0032] In the humidifying laminate, it is preferred that the nonporous film is applied so as to cover at least one surface of the porous reinforcing material.

[0033] In addition, the present disclosure provides a humidifier, which is provided with a plurality of bag-shaped water-retaining containers formed by bonding the above-mentioned humidifying laminate and a frame. The above-mentioned humidifier is formed by the above-mentioned humidifying laminate, so even if the non-porous membranes are arranged close to each other, the adhesion of the non-porous membranes can be suppressed, so when used in the humidifier, the humidifier can be easily miniaturized.

[0034] Furthermore, the present disclosure provides an air conditioner equipped with the above-mentioned humidifier.

[0035] Furthermore, the present disclosure provides a ventilation device equipped with the above-mentioned humidifier.

[0036] In addition, the present disclosure provides an air purifier equipped with the above-mentioned humidifier.

[0037] Beneficial Effects

[0038] The humidification laminate of the present disclosure can suppress the adhesion of the non-porous films. As a result, when used as a humidifier, the non-porous films can be arranged close to each other, so the humidifier can be miniaturized and the manufacturing cost can be suppressed. Therefore, the humidification laminate of the present disclosure is preferably used for a moisture permeable membrane humidifier. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic cross-sectional view showing one embodiment of the humidification laminate of the present disclosure. DETAILED DESCRIPTION

[0040] [Laminate for humidification]

[0041] The humidifying laminate of one embodiment of the present disclosure at least has: a porous reinforcing material; and a non-porous membrane, which is provided on at least one surface of the porous reinforcing material. The non-porous membrane can be provided on a single side of the reinforcing material, or on both sides. In addition, the humidifying laminate can also be a structure in which the non-porous membrane is clamped by two of the porous reinforcing materials. That is, the porous reinforcing material can also be provided on both sides of the non-porous membrane. In this case, the two porous reinforcing materials can be the same porous reinforcing materials, or they can be porous reinforcing materials with different materials, thicknesses, etc.

[0042] Figure 1 1 is a schematic cross-sectional view showing one embodiment of the humidifying laminate of the present disclosure. The humidifying laminate 1 includes a porous reinforcing material 11 and a non-porous membrane 12 provided on one surface 11 a of the porous reinforcing material 11 .

[0043] <Non-porous membrane>

[0044] The above-mentioned non-porous film functions as a moisture permeable film. In addition, the above-mentioned non-porous film surface has hydrophobicity and a concavo-convex shape. Thus, by reducing the contact area when the non-porous films contact each other, adhesion can be prevented. In addition, even if the non-porous films are bonded to each other, they are easily peeled off again, so the adhesion of the non-porous films to each other can be prevented.

[0045] The nonporous film preferably contains an anti-blocking agent. By containing the anti-blocking agent, it is easy to form a concavo-convex shape on the surface of the nonporous film, and it is easy to suppress the blocking of the nonporous films when the nonporous films are in contact with each other.

[0046] The average particle size of the anti-blocking agent is preferably 0.5 μm to 5 μm, more preferably 1 μm to 4 μm, and particularly preferably 1.5 μm to 3 μm.

[0047] The thickness of the non-porous film is not particularly limited, preferably 0.5 μm to 5 μm, more preferably 1 μm to 4 μm. If the thickness is 0.5 μm or more, the film-forming property becomes good, which is related to the improvement of gas barrier properties. In addition, the non-porous film has a tendency to be thick and excellent in moisture permeability. It is speculated that the reason is that the water content of the non-porous film is high. In addition, if the thickness is 5 μm or less, it is easy to form a film, and the economy is also excellent.

[0048] In addition, the average particle size of the anti-blocking agent is preferably larger than the thickness of the non-porous film, more preferably 0.1 μm to 3 μm larger than the thickness of the non-porous film, and particularly preferably 0.3 μm to 2 μm larger than the thickness of the non-porous film. By making the average particle size of the anti-blocking agent larger than the thickness of the non-porous film, it is easy to form a concavo-convex shape on the surface of the non-porous film. As an upper limit, from the viewpoint of the ease of forming the non-porous film, it is preferably 3 μm or less.

[0049] In addition, the concavo-convex shape on the surface of the non-porous film is preferably formed by the anti-blocking agent. It should be noted that, as long as the concavo-convex shape is formed on the surface of the non-porous film, the average particle size of the anti-blocking agent can be smaller than the thickness of the non-porous film, or it can be free of the anti-blocking agent. By making the average particle size of the anti-blocking agent larger than the thickness of the non-porous film, it is easy to give the concavo-convex shape on the surface of the non-porous film, and the contact area when the film contacts each other can be reduced, so bonding can be suppressed.

[0050] The arithmetic mean roughness (Sa) of the nonporous membrane surface is preferably 0.1 μm to 0.5 μm, more preferably 0.15 μm to 0.45 μm, and particularly preferably 0.2 μm to 0.4 μm. By making the arithmetic mean roughness (Sa) of the nonporous membrane surface 0.1 μm or more, the nonporous membrane surface can be given a sufficient concavoconvex shape. In addition, by making the arithmetic mean roughness (Sa) of the nonporous membrane surface 0.5 μm or less, it is easy to form a nonporous membrane.

[0051] As the above-mentioned anti-adhesion agent, preferably fluorine-based, silicon dioxide-based and chitosan-based anti-adhesion agents. In addition, as the above-mentioned anti-adhesion agent, it is preferably included in combination with the release agent described later. By using the above-mentioned anti-adhesion agent, it is also possible to easily suppress the adhesion of the above-mentioned non-porous film and the above-mentioned porous reinforcing material. As the above-mentioned anti-adhesion agent, silicon dioxide-based and chitosan-based are more preferably used. The above-mentioned anti-adhesion agent can be used only one, or two or more can be used in combination.

[0052] As the above-mentioned fluorine-based anti-adhesive agent, triperfluorooctyl phosphate and triperfluorododecyl phosphate can be listed. As the silica-based anti-adhesive agent, natural silica particles and synthetic silica particles can be listed. As the above-mentioned chitosan-based anti-adhesive agent, for example, chitosan nanofibers can be listed.

[0053] The content of the anti-blocking agent is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and particularly preferably 1 to 3 parts by mass relative to the total amount (100 parts by mass) of the copolymer. By making the anti-blocking agent the above content, it is easy to take into account both sufficient anti-blocking performance and moisture permeability.

[0054] The non-porous film may also include a release agent. As the release agent, a silicone-based release agent may be cited. The release agent exerts a release effect in the non-porous film. In the present disclosure, the release effect refers to the property of being easy to peel off again after bonding. By using a material that exerts the release effect, the non-porous film has hydrophobicity, which can make it easy to peel off again after the non-porous films are in contact with each other.

[0055] Examples of silicone-based release agents include dimethyl polysiloxane, etc. The silicone-based release agents may be modified, and examples of modified silicones include amino-modified silicones, epoxy-modified silicones, and hydrophilic polyether-modified silicones, etc. The release agents may be used alone or in combination of two or more.

[0056] The content of the release agent is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, and particularly preferably 1 to 3 parts by mass relative to the total amount (100 parts by mass) of the copolymer. By making the release agent the above content, it is easy to achieve both sufficient water repellency and moisture permeability.

[0057] The water contact angle of the nonporous membrane surface is preferably 90° to 120°, more preferably 92° to 110°. When the water contact angle of the nonporous membrane surface is 90° to 120°, the nonporous membrane can easily exhibit water repellency.

[0058] The non-porous film is a moisture permeable film, and in order to make the non-porous film absorb moisture, it is preferably composed of a thermoplastic resin. The thermoplastic resin preferably has a hydrophilic portion. In addition, in order to impart hydrophobicity to the surface of the non-porous film and form a water-conducting passage in the non-porous film, it is preferred that a hydrophobic portion is provided in the thermoplastic resin. Therefore, the thermoplastic resin preferably has both a hydrophilic portion and a hydrophobic portion. It is inferred that: in the non-porous film, by forming a structure in which the hydrophilic portion is separated from the hydrophobic portion, the hydrophilic portion functions as a water-conducting passage, which enables more water vapor to pass through, and thus the moisture permeability is more excellent.

[0059] Examples of the thermoplastic resin include acrylic resins, cellulose resins, polyester resins such as polybutylene terephthalate, polyether resins, polyurethane resins, polyvinyl chloride resins, polyethylene, polystyrene resins, polyamide resins, polyacetal resins, polycarbonate resins, polyphenylene sulfide resins, polyetheretherketone, polyimide resins, polytetrafluoroethylene resins, polycaprolactone, and polylactic acid.

[0060] As described above, the thermoplastic resin preferably has a hydrophilic part and a hydrophobic part, and therefore is preferably a thermoplastic copolymer containing different monomer components.

[0061] The hydrophilic part is preferably composed of a monomer (a) (hereinafter referred to as monomer (a)) unit containing a hydrophilic functional group in a side chain in the structural unit of the copolymer. In addition, the hydrophobic part is preferably composed of a monomer (b) (hereinafter referred to as monomer (b)) unit containing a hydrophobic functional group in a side chain. In addition, the hydrophilic part and the hydrophobic part are preferably formed in the copolymer. In the non-porous film, the copolymer can maintain a core-shell structure in which the hydrophobic part is formed inside and the hydrophilic part is formed outside. In this case, the hydrophilic part and the hydrophobic part can be formed by the core and shell of two or more adjacent copolymers. In addition, the copolymer can also be a core-shell structure before the non-porous film is formed, and the core-shell structure is not maintained when the non-porous film is formed.

[0062] The copolymer preferably contains a structural unit derived from the monomer (a) as a part constituting the hydrophilic part. As the monomer (a), for example, there can be listed: a monomer containing a glycidyl group, a monomer containing a hydrolyzable silyl group, a monomer containing an acetoacetyl group, a monomer containing a hydroxyl group, a monomer containing a carboxyl group, methyl (meth)acrylate, and a monomer having a cationic functional group described later. Among them, preferably a monomer containing a carboxyl group, methyl (meth)acrylate, and a monomer having a cationic functional group described later. The monomer (a) can be used alone or in combination of two or more. It should be noted that "(meth)acrylic acid" in this specification means at least one of "acrylic acid" and "methacrylic acid".

[0063] As said glycidyl group-containing monomer, glycidyl (meth)acrylate, (meth)allyl glycidyl ether, etc. are mentioned, for example.

[0064] Examples of the hydrolyzable silyl group-containing monomer include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, and vinyl methyl dimethoxysilane; and (meth) acryloxy silyl group-containing monomers such as γ-(meth)acryloxypropyl trimethoxysilane, γ-(meth)acryloxypropyl methyl dimethoxysilane, γ-(meth)acryloxypropyl triethoxysilane, and γ-(meth)acryloxypropyl methyl diethoxysilane.

[0065] Examples of the acetoacetyl group-containing monomer include allyl diacetoacetate, acetoacetoxyethyl (meth)acrylate, acetoacetoxyethyl crotonate, acetoacetoxypropyl (meth)acrylate, acetoacetoxypropyl crotonate, and 2-cyanoacetoacetoxyethyl (meth)acrylate.

[0066] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0067] Examples of the carboxyl group-containing monomer include acid anhydride monomers such as crotonic acid, maleic acid, and maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamide N-glycolic acid, cinnamic acid, and (meth)acrylic acid.

[0068] Furthermore, as the monomer (a), methyl (meth)acrylate and / or (meth)acrylic acid are particularly preferred. That is, the hydrophilic portion preferably includes a structural unit represented by the following formula (1).

[0069] [Chemical formula 1]

[0070]

[0071] (R1 and R2 each independently represent a hydrogen atom or a methyl group.)

[0072] The content of the monomer (a) is preferably 20 to 70 mol%, more preferably 30 to 70 mol%, and further preferably 40 to 60 mol% relative to the total monomer components constituting the copolymer. By adjusting the content of the monomer (a) within this range, a hydrophilic portion can be formed in the nonporous membrane to easily form a water-conducting path, and the moisture permeability is further improved.

[0073] The copolymer preferably contains a structural unit derived from the monomer (b) as a part constituting the hydrophobic portion. The monomer (b) is not particularly limited, but preferably contains a monomer having a hydrocarbon group with a carbon number of 2 or more, and more preferably, a (meth)acrylate having a hydrocarbon group with a carbon number of 2 or more can be cited. The monomer (b) can be used alone or in combination of two or more.

[0074] Examples of the hydrocarbon group having 2 or more carbon atoms include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a group in which two or more of these are bonded to each other.

[0075] Examples of the aliphatic hydrocarbon group include alkyl, alkenyl, and alkynyl. Examples of the alkyl group include straight or branched alkyl groups such as ethyl, propyl, isopropyl, butyl, isobutyl, hexyl, octyl, isooctyl, decyl, dodecyl, and stearyl. Examples of the alkenyl group include straight or branched alkenyl groups such as vinyl, allyl, methallyl, 1-propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, and 5-hexenyl. Examples of the alkynyl group include straight or branched alkynyl groups such as ethynyl and propynyl.

[0076] Examples of the alicyclic hydrocarbon group include cycloalkyl groups having 3 to 12 carbon atoms such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cyclododecyl; cycloalkenyl groups having 3 to 12 carbon atoms such as cyclohexenyl; and bridged hydrocarbon groups having 4 to 15 carbon atoms such as bicycloheptyl and bicycloheptenyl.

[0077] Examples of the aromatic hydrocarbon group include aryl groups having 6 to 14 carbon atoms (particularly aryl groups having 6 to 10 carbon atoms), such as phenyl and naphthyl.

[0078] The hydrocarbon group having 2 or more carbon atoms is preferably an aliphatic hydrocarbon group or an aromatic hydrocarbon group, and more preferably a linear or branched alkyl group or an aromatic hydrocarbon group.

[0079] Specifically, the monomer (b) is preferably a monomer capable of forming a structural unit represented by the following formula (2) and / or the following formula (3). That is, the hydrophobic portion preferably includes a structural unit represented by the following formula (2) and / or the following formula (3).

[0080] [Chemical formula 2]

[0081]

[0082] (R1 represents a hydrogen atom or a methyl group, and R3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms.)

[0083] [Chemical formula 3]

[0084]

[0085] (R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.)

[0086] In the above formula (2), the bonding position of R3 may be any of the hydrocarbons constituting the benzene ring. Examples of monomers capable of forming the structural unit represented by the above formula (2) include styrene, α-methylstyrene, p-methylstyrene, p-ethylstyrene, and the like.

[0087] In the above formula (3), R4 is preferably a branched alkyl group having 3 to 10 carbon atoms. Examples of the monomer capable of forming the structural unit represented by the above formula (3) include isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0088] The content of the monomer (b) is preferably 20 mol% to 70 mol%, more preferably 30 mol% to 70 mol%, and further preferably 40 mol% to 60 mol% relative to the total monomer components constituting the copolymer. By preparing the content of the monomer (b) within this range, water repellency can be exerted, and a water-conducting path can be easily formed by forming a hydrophobic portion in the non-porous film, and the moisture permeability is more excellent.

[0089] The above-mentioned thermoplastic resin preferably has a cationic part. In this case, the cationic part may be present in the above-mentioned hydrophilic part and / or the above-mentioned hydrophobic part, or may be present in other places. In addition, the above-mentioned thermoplastic resin preferably has a cationic part in the hydrophilic part. The above-mentioned cationic part is preferably a cationic functional group or a group that can generate a cationic functional group. The above-mentioned group that can generate a cationic functional group refers to a group that does not have a cationic functional group at the stage of the above-mentioned thermoplastic resin, but generates a cationic functional group at the stage of forming the above-mentioned non-porous membrane and when used. In addition, the above-mentioned cationic functional group may also be a zwitterionic functional group that has both cations and anions. Therefore, the above-mentioned thermoplastic resin may have an anionic part. In addition, the above-mentioned thermoplastic resin preferably does not have an anionic part.

[0090] As the above-mentioned cationic functional group, for example, a nitrogen-containing group can be listed. As the above-mentioned nitrogen-containing group, a group containing ammonium ions or a group capable of forming ammonium ions can be listed. Here, the above-mentioned group capable of forming ammonium ions refers to a group that is not ionized at the stage of the above-mentioned thermoplastic resin, and forms an ionized body at the stage of forming the above-mentioned non-porous membrane and when used. As the above-mentioned group containing ammonium ions and the group capable of generating ammonium ions, for example, cyclic groups containing nitrogen atoms such as primary amino groups, secondary amino groups, tertiary amino groups, quaternary ammonium groups, imino groups (-NH- groups and =NH groups), amidine groups, imino groups, hydrazine groups, amide groups, imide groups, pyridyl groups, etc. can be listed. In addition, as the above-mentioned zwitterionic functional group, for example, a quaternary ammonium-containing group can be listed. As the above-mentioned quaternary ammonium-containing group, for example, a betaine group, a phosphorylcholine group, etc. can be listed. Among the above thermoplastic resins, from the viewpoint of exerting antibacterial properties and preventing bacteria from flying from the nonporous film, groups capable of generating ammonium ions after the nonporous film is formed are preferred, and groups capable of generating quaternary ammonium groups (quaternary ammonium groups, imide groups) are more preferred.

[0091] When the thermoplastic resin is the copolymer, the copolymer preferably contains a structural unit derived from a monomer having a cationic functional group in a side chain. Examples of the monomer having a cationic functional group include monomers having the nitrogen-containing group as a functional group. Examples of the monomer having the nitrogen-containing group as a functional group include amide group-containing monomers, amino group-containing monomers, and imide group-containing monomers. Examples of the amide group-containing monomer include: N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and the like N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and the like N-alkyl (meth)acrylamide; N-vinylacetamide, N-(2-hydroxyethyl) (meth)acrylamide, N- N-hydroxyalkyl (meth)acrylamide such as amine, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, and N-(4-hydroxybutyl) (meth)acrylamide; N-alkoxyalkyl (meth)acrylamide such as N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; and N,N-dimethylaminopropyl (meth)acrylamide and N-(meth)acryloyl morpholine. In addition, examples of amino group-containing monomers include substituted or unsubstituted amino group-containing (meth)acrylates such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate. In addition, examples of monomers containing an imide group include N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyhexamethylene succinimide, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide. The above monomers having a cationic functional group may be used alone or in combination of two or more.

[0092] The content of the monomer having a cationic functional group is preferably 0.5 mol% to 10 mol%, more preferably 1 mol% to 7 mol%, and further preferably 2 mol% to 5 mol% relative to all monomer components constituting the copolymer. By preparing the content of the monomer having a cationic functional group within this range, repulsion with scale components can be exerted, and adhesion / accumulation of scale components to the non-porous membrane can be suppressed.

[0093] In addition, the above-mentioned copolymer may also contain a structural part derived from a crosslinking agent. As the above-mentioned crosslinking agent, as long as it is a compound that can be crosslinked with the side chain of the monomer constituting the above-mentioned copolymer, there is no particular limitation. For example, a difunctional body preferably has two reactive functional groups. From the viewpoints of increasing the width of the density of the crosslinking density in the polymer, adjusting the mechanical properties, etc., a trifunctional or higher crosslinking agent can be used. As the above-mentioned crosslinking agent, for example, difunctional or higher epoxy-containing compounds, difunctional or higher isocyanate-containing compounds, etc. can be listed. In the above-mentioned copolymer, from the aspect of being able to generate quaternary ammonium ions after the crosslinking reaction with the functional group formed in the side chain, it is particularly preferred to contain difunctional or higher epoxy-containing compounds.

[0094] Examples of the epoxy group-containing compound include bisphenol A and epichlorohydrin-type epoxy compounds, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, N,N,N',N'-tetraglycidyl-m-xylene diamine (e.g., trade name "TETRAD-X", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (e.g., trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0095] The amount of the crosslinking agent used is preferably 1 to 60 mol parts relative to the total amount (100 mol parts) of the reactive side chains of the copolymer, more preferably 2 to 30 mol parts, and further preferably 4 to 15 mol parts. By preparing the amount of the crosslinking agent used within this range, a water-conducting path can be easily formed in the nonporous film, making it easy to make the moisture permeability excellent.

[0096] The weight average molecular weight of the thermoplastic resin is not particularly limited, but is preferably 20,000 to 2,000,000, more preferably 30,000 to 1,500,000, further preferably 50,000 to 1,000,000, and particularly preferably 70,000 to 500,000. The weight average molecular weight is a value calculated based on polystyrene conversion by gel permeation chromatography (GPC).

[0097] The nonporous film may contain other components besides the thermoplastic resin within a range that does not impair the effects of the humidification laminate of the present disclosure.

[0098] The nonporous film may contain, for example, an antiseptic, a leveling agent, etc. as other components. The content of the other components is preferably 0.1 to 10 parts by mass, more preferably 0.15 to 3 parts by mass, and particularly preferably 0.2 to 2 parts by mass, relative to the total amount (100 parts by mass) of the thermoplastic resin.

[0099] The above-mentioned copolymer has a hydrophilic part and a hydrophobic part, causing the above-mentioned non-porous membrane to have a structure in which the hydrophilic part and the hydrophobic part are separated on the surface. The maximum diameter of the hydrophilic part in the above-mentioned non-porous membrane surface is preferably less than 50nm, more preferably less than 20nm. If the maximum diameter of the above-mentioned hydrophilic part is less than 50nm, the material with a size exceeding 50nm is not easy to penetrate the above-mentioned non-porous membrane, and the above-mentioned non-porous membrane can be used as a barrier film (barrier film) that does not allow materials (such as viruses, etc.) above 50nm to penetrate. The diameter of the above-mentioned hydrophilic part is evaluated by the following method. By using the adhesion measurement mode of a scanning probe microscope (SPM), the part with high adsorption force (hydrophilic part) and the part with low adsorption force (hydrophobic part) are digitized by adhesion, and processed using image analysis software, the diameter of the hydrophilic part can be calculated in the form of equivalent circle diameter. In addition, the above-mentioned maximum diameter is the diameter with the largest diameter in the diameter (equivalent circle diameter) of the hydrophilic part calculated as described above.

[0100] It should be noted that in the present disclosure, the structure in which the maximum diameter of the hydrophilic portion is below 50nm does not substantially penetrate components of a size of 50nm or more, and therefore substantially only penetrates water vapor, so the pores of the non-porous membrane in the present disclosure do not include pores below 50nm formed in the hydrophilic portion. In addition, when the maximum diameter of the hydrophilic portion exceeds 50nm, there is a possibility of permeating other components other than water vapor, and therefore a membrane having a structure in which the maximum diameter of a plurality of the hydrophilic portions exceeds 50nm is defined as a porous membrane.

[0101] The non-porous film is preferably a layer formed by coating. Since it is formed by coating, it can be easily made into a non-porous film, and it is easy to suppress the scattering of scale components, bacteria, etc.

[0102] <Porous reinforcement material>

[0103] Preferably, the porous reinforcing material is an element that serves as a support for the nonporous membrane and has excellent moisture permeability.

[0104] As the material forming the above-mentioned porous reinforcing material, any one of hydrophilic material and hydrophobic material can be used, but hydrophobic material is preferably used.If the above-mentioned hydrophobic material is used, when the composition for forming a non-porous film is applied, the composition does not penetrate into the porous reinforcing material, so in the porous reinforcing material, there is no need to prevent the guiding substrate from flowing down from the face opposite to the film forming face.

[0105] As the material forming the above-mentioned porous reinforcing material, for example, can be listed: organic matter such as polyolefin resin, cellulose resin, polycarbonate resin, polyamide resin, polyimide resin, polyamide-imide resin and fluorine resin, inorganic matter such as metal, glass and ceramic etc.Wherein, because the above-mentioned non-porous film can be made into film with lower temperature on the above-mentioned porous reinforcing material, in addition, from the viewpoint of excellent moisture permeability and water resistance, it is preferably organic matter, as the above-mentioned organic matter, it is particularly preferably polyolefin resin.The above-mentioned material can also be fibrous such as metal fiber, inorganic fiber.The material forming the above-mentioned porous reinforcing material can be only one kind, can also be two or more.

[0106] Examples of the porous reinforcing material include a resin porous film, an inorganic porous film, a metal porous film, and a fibrous substrate.

[0107] The polyolefin resin is a polymer (including an olefin elastomer) composed of an olefin as an essential monomer component, that is, a polymer containing at least a structural unit derived from an olefin in a molecule (in one molecule). The olefin is not particularly limited, and examples thereof include α-olefins such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene.

[0108] Examples of the polyolefin resin include polymers containing ethylene as an essential monomer component (polyethylene resins), polymers containing propylene as an essential monomer component (polypropylene resins), ionomers, and amorphous cyclic olefin polymers.

[0109] The porosity of the porous reinforcing material is not particularly limited, but is preferably 30% to 90% by volume, more preferably 40% to 70% by volume. If the porosity is 30% by volume or more, the moisture permeability becomes better. If the porosity is 90% by volume or less, the supporting performance of the nonporous membrane becomes better.

[0110] The thickness of the porous reinforcing material is not particularly limited, but from the viewpoint of fully supporting the nonporous film, it is preferably more than 5 μm, more preferably more than 10 μm. In addition, considering excellent moisture permeability and economy, the thickness of the porous reinforcing material is preferably less than 50 μm, more preferably less than 30 μm.

[0111] From the viewpoint of being able to easily form the nonporous film, the surface of the porous reinforcing material on the side having the nonporous film (for example, Figure 1 The surface 11a shown in (11) is preferably hydrophilized. Particularly, when a hydrophobic material is used as the material forming the above-mentioned porous reinforcing material, the above-mentioned hydrophilization is preferably implemented. As the above-mentioned hydrophilization, corona discharge treatment, plasma treatment, etc. can be listed. Through these hydrophilization, carboxyl, hydroxyl or carbonyl can be generated on the porous reinforcing material surface, and the composition used to form the above-mentioned non-porous film is easily wetted and expanded on the porous reinforcing material surface, and the above-mentioned non-porous film is easily formed. In addition, thus, the adhesion of the above-mentioned porous reinforcing material and the above-mentioned non-porous film is improved. In addition, when the above-mentioned porous reinforcing material formed by the hydrophobic substrate is kept as a winding body, the form in which one face of the above-mentioned porous reinforcing material contacts with the other face in the winding body, but because a hydrophilic face contacts with the hydrophobic other face, adhesion can be prevented.

[0112] The surface tension of the surface of the porous reinforcing material on one side of the non-porous film is preferably 35dyn / cm to 55dyn / cm, and more preferably 37dyn / cm to 50dyn / cm. If the surface tension is 35dyn / cm or more, it is easy to apply the composition for forming the non-porous film, and it is easy to form the non-porous film. If the surface tension is 55dyn / cm or less, the composition for forming the non-porous film can not be excessively wetted and expanded, and the non-porous film can be easily formed on the surface of the porous reinforcing material. It should be noted that when the surface of the porous reinforcing material is hydrophilized, the surface on one side of the non-porous film is the surface to which the hydrophilization treatment is applied.

[0113] The surface tension of the inside of the above-mentioned porous reinforcing material (that is, the inside of the region where the above-mentioned non-porous film is not formed) is preferably less than 35dyn / cm, more preferably less than 33dyn / cm. If the above-mentioned surface tension is less than 35dyn / cm, the composition for forming the above-mentioned non-porous film can be suppressed from penetrating into the inside of the above-mentioned porous reinforcing material, and the above-mentioned non-porous film is easily formed on the surface of the above-mentioned porous reinforcing material. It should be noted that, when the surface of the above-mentioned porous reinforcing material has been hydrophilized, the inside of the above-mentioned porous reinforcing material is the inside of the region where the hydrophilization treatment is not implemented. In addition, the surface tension of the above-mentioned inside can be obtained by measuring the cross section obtained by cutting off the above-mentioned porous reinforcing material.

[0114] The humidifying laminate is preferably heated at 70°C for 15 hours in a rolled sheet, and when the sheet is pulled out by hand, adhesion is suppressed between the non-porous membranes, between the porous reinforcing materials, or between the non-porous membrane and the porous reinforcing material. In the case of a humidifying laminate having a non-porous membrane formed on one side of the porous reinforcing material, adhesion is preferably suppressed between the non-porous membrane and the porous reinforcing material. The humidifying laminate is easy to manufacture and store as a wound body by suppressing adhesion in the above-mentioned various schemes.

[0115] In the two humidifying laminates made of 25mm×100mm strips of the above-mentioned humidifying laminate having the above-mentioned non-porous film on at least one surface, water is dripped onto the non-porous film side of one humidifying laminate, and the non-porous film side of the other humidifying laminate is laminated so that water is spread over the entire surface. The laminated humidifying laminate is heated at 55°C for 1 hour, and the peel strength when the peel strength is measured by Tensilon is preferably 3N / 25mm or less, more preferably 2N / 25mm or less, and further preferably 0.5N / 25mm or less. By making the above-mentioned peel strength less than 3N / 25mm, it is easy to peel off again even if the above-mentioned non-porous films are in contact with each other, and it is easy to suppress adhesion.

[0116] In addition, the water retention capacity of the humidification laminate is preferably 8 g / m 2 More preferably 15g / m 2 Above, particularly preferably 15g / m 2 It should be noted that the water retention in the present disclosure refers to the water retention per 1m when the non-porous membrane is cut into a circle with a diameter of 7 cm and immersed in pure water for 15 minutes. 2 The amount of the humidifying laminate of the test piece is increased. By making the water retention of the humidifying laminate 8g / m 2 As described above, sufficient moisture permeability can be easily exhibited.

[0117] [Method for producing a humidifying laminate]

[0118] The disclosed humidification laminate can be made by forming the above-mentioned non-porous film using a known or customary method on at least one surface of the above-mentioned porous reinforcing material.For example, the above-mentioned non-porous film can be directly formed on a surface of the above-mentioned porous reinforcing material, or after the above-mentioned non-porous film is temporarily formed on other supports, transfer (lamination) is applied to a surface of the above-mentioned porous reinforcing material, thus forming the above-mentioned non-porous film on the porous reinforcing material.Wherein, from the viewpoint of the excellent adhesion of the above-mentioned non-porous film and the above-mentioned porous reinforcing material, the method of the former is preferably used.

[0119] The surface of the porous reinforcing material on the side where the nonporous membrane is provided may be subjected to a hydrophilic treatment. Examples of the hydrophilic treatment include the above-mentioned treatments.

[0120] The nonporous film can be formed by coating (applying) the composition for forming the nonporous film onto the porous reinforcing material or the other support, and removing the solvent from the obtained coating film by heating or the like.

[0121] Since the porous reinforcing material is subjected to the hydrophilization treatment to suppress blocking, it can be produced by a roll-to-roll method in which a non-porous film is formed on the porous reinforcing material previously made into a rolled body and then the rolled body is made again.

[0122] The above-mentioned composition can be made by a known or customary method. For example, the above-mentioned copolymer can be made by dissolving or dispersing it in a solvent, and mixing additives such as preservatives as needed. As the above-mentioned solvent, water and / or a water-soluble solvent are preferred. It can be inferred that when water or a water-soluble solvent is used, the above-mentioned copolymer is dispersed in the composition in a core-shell shape with the inner side being the hydrophobic portion and the outer side being the hydrophilic portion. By using such a composition, the hydrophilic portion is separated from the hydrophobic portion when the coating is dried, and a non-porous film is formed in a state with a water-conducting channel. In addition, it can be inferred that the hydrophobic portion becomes a state of being firmly bonded to each other, and water resistance becomes better.

[0123] Examples of the water-soluble solvent include aliphatic water-soluble alcohols such as methanol, ethanol, n-propanol, and isopropanol; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether; and the like. The water-soluble solvent may be used alone or in combination of two or more.

[0124] The ratio (concentration) of the above-mentioned copolymer in the above-mentioned composition in which the above-mentioned copolymer is dissolved or dispersed is not particularly limited, and is preferably 0.5 to 5% by mass, more preferably 1 to 4% by mass, and further preferably 1.5 to 3% by mass. If the above-mentioned concentration is less than 5% by mass, the thickness of the coating layer thickens, so the film thickness of the non-porous film after drying is further uniformized. Thus, a non-porous film with excellent gas barrier properties and further thin filmization can be formed, and as a result, moisture permeability is further improved. In addition, if the above-mentioned concentration is within the above-mentioned range, the coating property is excellent, and in addition, a non-porous film with excellent moisture permeability and gas barrier properties is easily formed.

[0125] It should be noted that the coating (applying) of the above-mentioned composition can also utilize known coating methods. For example, coating machines such as gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, spray coater, comma coater, direct coater, etc. can also be used. Formed by such coating, thus easily form a non-porous film.

[0126] The heating temperature when the above-mentioned coating film is desolvated is preferably 35°C to 90°C, more preferably 40°C to 85°C, and further preferably 45°C to 80°C. The heating time can be appropriately used for an appropriate time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes. The above-mentioned composition can be used to form a non-porous film at a low temperature below 90°C (especially below 80°C), so it is easy to form a film. In addition, a polyolefin resin with excellent moisture permeability can be used as a porous reinforcing material.

[0127] The humidification stacking body that forms the above-mentioned non-porous film on at least one surface of the above-mentioned porous reinforcing material by the above-mentioned method has hydrophobicity and concavo-convex shape, so the adhesion of the non-porous films to each other can be suppressed, and the non-porous films can be arranged close to each other, so the humidifier can be further miniaturized. It should be noted that the above-mentioned humidification stacking body refers to a stacking body that can make water vapor move via the humidification stacking body. In addition, the above-mentioned humidification stacking body has a structure that the hydrophilic part and the hydrophobic part are separated, so it can also be used as a barrier film with moisture permeability. In the case where the diameter of the above-mentioned hydrophilic part is small, because as a barrier film with the above-mentioned moisture permeability, for a small-sized substance (such as water vapor) with hydrophilicity, it is passed through the hydrophilic part, and a substance with a large size (such as a virus) is not passed through the hydrophilic part, thus the two can be separated.

[0128] [Bag-shaped water-retaining container]

[0129] By covering the outside of the frame with the humidification laminate, a bag-shaped water-retaining container can be produced.

[0130] The frame is preferably made of a rigid material, such as resin, metal / alloy material, etc. In addition, the frame may be a plate-shaped or bag-shaped frame produced by extrusion molding, a plate-shaped frame produced by injection molding, or a bag-shaped structure produced by laminating two or more plate-shaped frames. In addition, the hole portion may be provided after the bag-shaped frame is produced, or a frame with the hole portion provided in advance may be produced.

[0131] Preferably, a part or the whole of the contact portion between the laminate and the frame is bonded. The method of bonding to the frame is not particularly limited, and the laminate can be bonded by bonding using a known or commonly used adhesive, or by welding using ultrasonic welding, high-frequency welding, thermal welding, or the like.

[0132] The above method can be used to make a bag-shaped water-retaining container. The bag-shaped water-retaining container has a stacked body arranged outside a frame structure, and the water of the liquid introduced into the bag-shaped water-retaining container is absorbed by the stacked body as water vapor, diffuses in the stacked body, and can release water vapor from the entire stacked body.

[0133] In addition, a humidifier can be manufactured by mounting a plurality of the bag-shaped water-retaining containers. Such a humidifier has improved humidification performance compared to the past, so it can achieve the same performance while miniaturizing the humidifier, and is also excellent in terms of cost.

[0134] Therefore, the humidifier can be miniaturized by including the humidifying laminate, and can be suitably used in applications such as air conditioners, ventilators, and air cleaners.

[0135] Each scheme disclosed in this specification may also be combined with any other feature disclosed in this specification. Each configuration and combination of configurations in each embodiment is an example, and appropriate addition, omission, substitution and other changes of configurations may be made within the scope of the present disclosure. In addition, each invention disclosed in this disclosure is not limited by the embodiments and the following examples, but only by the patent claims.

[0136] Example

[0137] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.

[0138] Example 1

[0139] To 100 parts by mass of a thermoplastic resin solution, silicone (trade name "X-51-1264", manufactured by Shin-Etsu Chemical Co., Ltd.) and silica fine particles (average particle size 1.7 μm, trade name "SYLYSIA 300", manufactured by Fuji SYLYSIA Chemical) were added, and diluted with 21 parts by mass of ethanol and 154 parts by mass of distilled water to prepare a coating solution. The thermoplastic resin solution contained: 47 parts by mass of isobutyl acrylate and 1 part by mass of styrene as structural units forming the hydrophobic part in the polymer; 21 parts by mass of acrylic acid and 28 parts by mass of methyl acrylate as structural units forming the hydrophilic part; 3 parts by mass of imide as structural units forming the cationic part; and 2 parts by mass of an epoxy compound as a crosslinking agent. On the other hand, one surface of a porous polypropylene substrate (thickness: 20 μm, porosity: 48% by volume) was subjected to corona treatment to form a hydrophilic surface with a surface tension of 39 dyn. Then, the coating solution was applied to the hydrophilic surface of the porous substrate using a wire rod, and heated at 70°C for 1 minute to form a non-porous film (thickness: 1 μm). In this way, the humidifying laminate of Example 1 was prepared. It should be noted that, in the humidifying laminate of Example 1, the average particle size of the silica particles is larger than the film thickness of the non-porous film, the concavo-convex shape is formed by the silica particles, and the water repellency is imparted by the silicone particles.

[0140] Examples 2, 3, Comparative Examples 1, 2

[0141] A humidifying laminate was produced in the same manner as in Example 1 except that the coating solution was prepared by adding the components marked with circle as shown in Table 1. In addition, each humidifying laminate produced had the concavo-convex shape shown in Table 1.

[0142] The details of each component in Table 1 other than the above are described below.

[0143] Silica fine particles B: trade name "MP-4540M", manufactured by Nissan Chemical Co., Ltd., average particle size 0.45 μm.

[0144] Chitosan: trade name "EFo-08002", manufactured by SUGINO MACHINE CO., LTD.

[0145] Chitosan is a nanofiber, not a particle, so the average particle size cannot be described. It is fine even if it is deleted from the examples, so if there is a preferred description method, please modify it.

[0146] [evaluate]

[0147] Each humidification laminate obtained in the examples and comparative examples was evaluated as follows. The evaluation results are shown in the table.

[0148] (1) Water contact angle

[0149] About 2 μL of distilled water was dropped onto the nonporous membrane surface of the obtained humidifying laminate using a contact angle measuring apparatus (trade name "DropMaster DMs-401", manufactured by Kyowa Interface Science Co., Ltd.), and the angles (contact angles) formed between the droplet and the surface at three points were measured. The average value was used as the water contact angle for evaluation.

[0150] (2) Arithmetic mean roughness (Sa)

[0151] In accordance with JIS B 0681, a non-contact surface / layer profile measurement system (trade name "VertScan 2.0", manufactured by Ryoka Systems Co., Ltd.) was used to measure the concavo-convex shape of the non-porous film surface with a 5x objective lens and a field of view of 2.51 mm×1.88 mm, and the arithmetic mean height (Sa) was calculated based on the obtained area.

[0152] (3)Water retention capacity

[0153] The nonporous membrane side of the humidifying laminate cut into a circle with a diameter of 7 cm was immersed in pure water for 15 minutes and taken out. The increase in mass of the humidifying laminate compared with that before the test was converted into per 1 m 2 The mass of the test piece was calculated as the water retention.

[0154] (4) Anti-blocking property (evaluation of roll state)

[0155] The humidifying laminate was rolled up and heated at 70°C for 15 hours, then unrolled by hand and the blocking property was evaluated as follows. It should be noted that this evaluation is an evaluation of the anti-blocking property of the non-porous film and the porous substrate in the humidifying laminate, and the following cases were evaluated as having anti-blocking property.

[0156] Large: The humidification laminate cannot be unwound.

[0157] Middle: After the humidifying laminate is unwound, the humidifying laminate is deformed.

[0158] Small: After the humidifying laminate was unwound, the humidifying laminate was not deformed at all.

[0159] (Evaluation of film status)

[0160] Two 25 mm × 100 mm long strips of the above-mentioned humidification laminate were prepared. After water was dripped onto the non-porous membrane side of one sample, the non-porous membrane of the other humidification laminate was laminated so that water was spread over the entire surface. The laminated sample was heated at 55° C. for 1 hour, and the peel strength was measured using a Tensilon. It should be noted that this evaluation is an evaluation of the anti-blocking property of the non-porous membrane surfaces in the humidification laminate, and the case below 3N / 25mm was evaluated as having anti-blocking property.

[0161] [Table 1]

[0162] (Table 1)

[0163]

[0164]

[0165] As shown in Examples 1 to 3, in the humidifying laminate having a non-porous membrane surface with hydrophobicity and a concavo-convex shape, it was confirmed that the blocking between the non-porous membranes was reduced. In addition, in the humidifying laminate having insufficient hydrophobicity and a small concavo-convex shape (Comparative Example 1) and the humidifying laminate having only hydrophobicity and a small concavo-convex shape (Comparative Example 2), blocking was confirmed.

[0166] Modifications of the invention disclosed herein will be described below.

[0167] [Note 1]

[0168] A humidifying laminate, comprising: a porous reinforcing material; and a non-porous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, wherein the surface of the non-porous film is water-repellent and has a concavo-convex shape.

[0169] [Note 2]

[0170] The humidifying laminate according to Supplementary Note 1, wherein the nonporous film contains an anti-blocking agent.

[0171] [Note 3]

[0172] The humidifying laminate according to Supplementary Note 2, wherein the average particle diameter of the anti-blocking agent is larger than the film thickness of the non-porous film, and the concavo-convex shape is formed by the anti-blocking agent.

[0173] [Note 4]

[0174] The humidifying laminate according to any one of Appendixes 1 to 3, wherein the water contact angle on the surface of the nonporous membrane is 90° to 120°.

[0175] [Note 5]

[0176] The humidifying laminate according to any one of Appendixes 1 to 4, wherein the arithmetic mean roughness (Sa) of the non-porous film surface is 0.1 μm to 0.5 μm.

[0177] [Note 6]

[0178] The humidifying laminate according to any one of Appendixes 1 to 5, wherein the nonporous membrane is disposed on the water side of the liquid with respect to the porous reinforcing material, and absorbs water from the liquid and releases it into the air.

[0179] [Note 7]

[0180] The humidifying laminate according to any one of Appendixes 1 to 6, wherein the nonporous film contains a thermoplastic resin having a cationic portion, and the cationic portion contains a group containing an ammonium ion or a group capable of forming an ammonium ion.

[0181] [Note 8]

[0182] The humidifying laminate according to any one of Appendixes 1 to 7, wherein the nonporous film contains a thermoplastic resin having a hydrophilic portion, and the hydrophilic portion contains a structural unit represented by the following formula (1).

[0183] [Chemical formula 1]

[0184]

[0185] (R1 and R2 each independently represent a hydrogen atom or a methyl group.)

[0186] [Note 9]

[0187] The humidifying laminate according to any one of Appendixes 1 to 8, wherein the nonporous film contains a thermoplastic resin having a hydrophobic portion, and the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3).

[0188] [Chemical formula 2]

[0189]

[0190] (R1 represents a hydrogen atom or a methyl group, and R3 represents an alkyl group having 1 to 2 carbon atoms.)

[0191] [Chemical formula 3]

[0192]

[0193] (R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.) [Supplementary Note 10]

[0194] The humidifying laminate according to any one of appendixes 1 to 9, wherein the water retention capacity is 5 g / m 2 ~30g / m 2 .

[0195] [Note 11]

[0196] The humidifying laminate according to any one of Appendixes 1 to 10, wherein the nonporous film is applied so as to cover at least one surface of the porous reinforcing material.

[0197] [Note 12]

[0198] A humidifier provided with a plurality of bag-shaped water-retaining containers formed by bonding the humidifying laminate according to any one of Supplementary Notes 1 to 11 to a frame.

[0199] [Note 13]

[0200] An air conditioner equipped with the humidifier as described in Supplementary Note 12.

[0201] [Note 14]

[0202] A ventilation device equipped with the humidifier as described in Appendix 12.

[0203] [Note 15]

[0204] An air purifier equipped with the humidifier as described in Appendix 12.

[0205] Description of Reference Numerals

[0206] 1: laminate;

[0207] 11: Porous reinforcement material;

[0208] 11a: One surface of the porous reinforcement material;

[0209] 12: Non-porous membrane.

Claims

1. A humidifying laminate, wherein: The laminated body comprises: a porous reinforcing material; and a non-porous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, The non-porous membrane surface is hydrophobic and has a concavo-convex shape.

2. The humidifying laminate according to claim 1, wherein The nonporous film includes an antiblocking agent.

3. The humidifying laminate according to claim 2, wherein The average particle size of the anti-blocking agent is larger than the thickness of the non-porous film. The concavo-convex shape is formed by the anti-adhesive agent.

4. The humidifying laminate according to claim 1 or 2, wherein The water contact angle on the surface of the non-porous membrane is 90° to 120°.

5. The humidifying laminate according to claim 1 or 2, wherein The arithmetic mean roughness Sa of the non-porous membrane surface is 0.1 μm to 0.5 μm.

6. The humidifying laminate according to claim 1 or 2, wherein The non-porous membrane is disposed on the water side of the liquid relative to the porous reinforcing material, and is used to absorb water from the liquid and release it into the air.

7. The humidifying laminate according to claim 1 or 2, wherein The nonporous film contains a thermoplastic resin having a cationic portion containing a group containing an ammonium ion or a group capable of forming an ammonium ion.

8. The humidifying laminate according to claim 1 or 2, wherein The nonporous film contains the thermoplastic resin having a hydrophilic portion, wherein the hydrophilic portion contains a structural unit represented by the following formula (1): [Chemical formula 1] In the formula, R1 and R2 each independently represent a hydrogen atom or a methyl group.

9. The humidifying laminate according to claim 1 or 2, wherein The nonporous film contains the thermoplastic resin having a hydrophobic portion, wherein the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3), [Chemical formula 2] In formula (2), R1 represents a hydrogen atom or a methyl group, and R3 represents an alkyl group having 1 to 2 carbon atoms. [Chemical formula 3] In formula (3), R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.

10. The humidifying laminate according to claim 1 or 2, wherein Water retention is 5g / m 2 ~30g / m 2 .

11. The humidifying laminate according to claim 1 or 2, wherein The non-porous film is applied so as to cover at least one surface of the porous reinforcing material. 12 . A humidifier comprising a plurality of bag-shaped water-retaining containers formed by bonding the humidifying laminate according to claim 1 or 2 to a frame.

13. An air conditioner equipped with the humidifier according to claim 12.

14. A ventilation device equipped with the humidifier according to claim 12.

15. An air purifier equipped with the humidifier according to claim 12.

Citation Information

Patent Citations

  • Humidifier

    JP1996233315A

  • Moving image encoding device and decoding device

    JP2022096879A

  • Aqueous composition, hard coat film, laminated film, transparent conductive film, and touch panel

    CN106376237A

  • High-brightness anti-adhesion brightness enhancement film and backlight module

    CN108627898A

  • Moisture-permeable waterproof film, composite material, and processes for producing these

    CN1723235A